Improved Hybrid Precoder Design for Secure mmWave MIMO Communications - Kabalci, Yasin; Ali, Muhammad (Elektronika ir elektrotechnika, 2020)
Key challenges of emerging mobile communication systems are to provide higher data rates, diverse device connectivity, low latency, higher system capacity, and low energy consumption. The communication systems exploiting the millimeter-wave (mmWave) band are realized to resolve thereof inevitable issues. However, security is considered as one of the challenging issues in mmWave communication in addition to unavoidable problems (e.g., propagation loss, penetration loss, and fading). This study aims to construct efficient secure hybrid precoder with low-resolution phase shifters that can protect legitimate information from eavesdropping by employing coordinated analog precoder and combiner algorithms and improve the secrecy rate. Moreover, in order to further enhance the secrecy rate, hybrid precoder are obtained using an efficient channel. This work compares its results with the recent approach reported in the literature, which indicates that our proposed model outperforms at high signal-to-noise ratio (SNR) values, while our model provides similar performance at low SNR values. Simulation studies also confirm the effectiveness of the proposed hybrid precoder to achieve maximum secrecy rate.